Inhibition of human CYP1 enzymes by a classical inhibitor α-naphthoflavone and a novel inhibitor N-(3, 5-dichlorophenyl)cyclopropanecarboxamide: An in vitro and in silico study - Risto Olavi Juvonen; Elmeri Matias Jokinen; Adeel Javaid; Marko Lehtonen; Hannu Raunio; Olli Taneli Pentikäinen (WILEY, 2022)
Enzymes in the cytochrome P450 family 1 (CYP1) catalyze metabolic activation of procarcinogens and deactivation of certain anticancer drugs. Inhibition of these enzymes is a potential approach for cancer chemoprevention and treatment of CYP1-mediated drug resistance. We characterized inhibition of human CYP1A1, CYP1A2, and CYP1B1 enzymes by the novel inhibitor N-(3,5-dichlorophenyl)cyclopropanecarboxamide (DCPCC) and alpha-naphthoflavone (ANF). Depending on substrate, IC50 values of DCPCC for CYP1A1 or CYP1B1 were 10-95 times higher than for CYP1A2. IC50 of DCPCC for CYP1A2 was 100-fold lower than for enzymes in CYP2 and CYP3 families. DCPCC IC50 values were 10-680 times higher than the ones of ANF. DCPCC was a mixed-type inhibitor of CYP1A2. ANF was a competitive tight-binding inhibitor of CYP1A1, CYP1A2, and CYP1B1. CYP1A1 oxidized DCPCC more rapidly than CYP1A2 or CYP1B1 to the same metabolite. Molecular dynamics simulations and binding free energy calculations explained the differences of binding of DCPCC and ANF to the active sites of all three CYP1 enzymes. We conclude that DCPCC is a more selective inhibitor for CYP1A2 than ANF. DCPCC is a candidate structure to modulate CYP1A2-mediated metabolism of procarcinogens and anticancer drugs.